Management strategies for regenerative agriculture based on the assessment of soil fertility in northern Mozambique - Nasukawa, Hisashi; Tajima, Ryosuke; Pereira, Maria Clarinda Filomena; Pedro, Joao Antonio; Nakamura, Satoshi; Fukuda, Monrawee; Koide, Junji; Oya, Tetsuji; Homma, Koki (Geoderma Regional, 2025)
Despite having high potential for agricultural production, the maize yield in northern Mozambique is low due to the depletion of macronutrients in soil. Soil fertility analysis serves as a basis for developing regenerative agriculture (RA) strategies. For best results, RA practices suitable to the type of soil in northern Mozambique should be selected and applied. Hence, in this study, we examined soil characteristics and their relationship with maize yield across 196 locations in the Nacala Corridor of northern Mozambique. The results revealed significant variation in soil fertility, which was primarily influenced by organic matter, clay content, and nutrient availability. Cluster analysis identified three distinct soil fertility groups: low-fertility soils were found in the eastern region, with reduced maize yield, whereas high-fertility soils were predominant in the western and central-southern regions, which produced better yield. These findings highlight the importance of detailed soil analysis for the development of targeted soil management strategies, such as conservation agriculture and integrated soil fertility management, that can enhance nutrient retention, increase organic matter content, and improve crop yield. This study provides essential insights for smallholder farmers and policymakers to implement sustainable agriculture and improve long-term productivity in northern Mozambique.